LINGUOCULTUROLOGY AS AN INDEPENDENT DIRECTION OF LINGUISTICS (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The article pays great attention to the concept of linguoculturology and explores the inextricable interconnection of a number of sciences. Linguoculturology analyzes the mental, cultural and mental characteristics of representatives of different ethnic groups, which makes it possible to identify the characteristics of their cultural values, the specifics of the concepts of the material and inner world of a person. Particular attention is paid to the concepts of “concept” and “conceptosphere”; through the concept, a person develops an image of his native language, his thesaurus is created, and through the concept sphere, a person realizes himself as a linguistic personality.